Fibroblast Growth Factor 21 Prevents Atherosclerosis by Suppression of Hepatic Sterol Regulatory Element-Binding Protein-2 and Induction of Adiponectin in Mice. Issue 21 (26th May 2015) - Lin, Zhuofeng; Pan, Xuebo; Wu, Fan; Ye, Dewei; Zhang, Yi; Wang, Yu; Jin, Leigang; Lian, Qizhou; Huang, Yu; Ding, Hong; Triggle, Chris; Wang, Kai; et al.
<x xml:space="preserve">Abstract</x> Background— Fibroblast growth factor 21 (FGF21) is a metabolic hormone with pleiotropic effects on glucose and lipid metabolism and insulin sensitivity. It acts as a key downstream target of both peroxisome proliferator-activated receptor α and γ, the agonists of which have been used for lipid lowering and insulin sensitization, respectively. However, the role of FGF21 in the cardiovascular system remains elusive. Methods and Results— The roles of FGF21 in atherosclerosis were investigated by evaluating the impact of FGF21 deficiency and replenishment with recombinant FGF21 in apolipoprotein E−/− mice. FGF21 deficiency causes a marked exacerbation of atherosclerotic plaque formation and premature death in apolipoprotein E−/− mice, which is accompanied by hypoadiponectinemia and severe hypercholesterolemia. Replenishment of FGF21 protects against atherosclerosis in apolipoprotein E−/−mice via 2 independent mechanisms, inducing the adipocyte production of adiponectin, which in turn acts on the blood vessels to inhibit neointima formation and macrophage inflammation, and suppressing the hepatic expression of the transcription factor sterol regulatory element-binding protein-2, thereby leading to reduced cholesterol synthesis and attenuation of hypercholesterolemia. Chronic treatment with adiponectin partially reverses atherosclerosis without obvious effects on hypercholesterolemia in FGF21-deficient apolipoprotein E−/− mice. By contrast, the cholesterol-lowering effects of FGF21 are abrogated by hepatic expression of sterol regulatory element-binding protein-2. Conclusions— FGF21 protects against atherosclerosis via fine tuning the multiorgan crosstalk among liver, adipose tissue, and blood vessels.